Interior material and method for producing the same
Patent Information
- Application Number
- JP2024207900
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-03-30
Smart Images

Figure 2025023106000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an interior material including a substrate and an active energy ray-curable resin layer laminated on the substrate, and a method for producing the same. [Background technology]
[0002] 2. Description of the Related Art Interior materials such as flooring and wall materials have low gloss surfaces.
[0003] One such type of interior material that has been proposed is a decorative sheet (interior material) in which a layer of ultraviolet-cured resin containing powder such as silica is laminated onto a base material, with the powder forming a fine uneven structure on the surface (see, for example, Patent Document 1).
[0004] In addition, decorative sheets (interior materials) and building materials (interior materials) have been proposed in which a coating liquid containing an ultraviolet-curable resin is applied to a substrate, the surface of the coating liquid is partially cured by irradiating with excimer laser light, and then the entire coating liquid is cured by irradiating with ultraviolet light, thereby forming an ultraviolet-curable resin having a fine uneven structure on the surface (see, for example, Patent Documents 2 and 3). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2021-165033 A [Patent Document 2] Patent Publication No. 2021-24102 [Patent Document 3] JP 2018-164901 A Summary of the Invention [Problem to be solved by the invention]
[0006] There is a demand for interior materials that are excellent in low gloss and stain resistance. In this regard, the interior materials of Patent Documents 1 to 3 can achieve low gloss by forming an uneven structure, but the stain resistance expressed by a heel mark test (hereinafter, simply referred to as "stain resistance") is insufficient. This is because there is a trade-off between low gloss and stain resistance.
[0007] The present invention has been made in consideration of the above problems, and has an object to provide an interior material that achieves both low gloss and stain resistance, and a method for producing the same. [Means for solving the problem]
[0008] The characteristic configuration of the interior material according to the present invention for solving the above problems is as follows: An interior material comprising a substrate and an active energy ray-cured resin layer laminated on the substrate, the active energy ray-curable resin layer being made of a cured product of an active energy ray-curable resin composition, The surface of the active energy ray-curable resin layer has an uneven structure that satisfies the following surface roughness parameters (1) to (3). (1) The arithmetic mean height (Sa) is 0.5 to 6 μm. (2) The average arithmetic curvature (Spc) of the tip of the convex part is 300 to 1300 μm. -1 It is. (3) When the projected area of the uneven structure projected onto a flat surface is S1 and the difference between the actual surface area of the uneven structure and the projected area S1 is S2, the developed area ratio (Sdr) represented by S2 / S1 is 0.05 to 0.2.
[0009] The interior material of this configuration includes a substrate and an active energy ray-cured resin layer laminated on the substrate and made of a cured product of an active energy ray-curable resin composition. The surface of the active energy ray-cured resin layer has an uneven structure that satisfies the surface roughness parameters (1) to (3) above. As a result, the uneven structure on the surface of the active energy ray-cured resin layer is suitable for exhibiting both low gloss and stain resistance in terms of the degree of protrusion (protrusion length) of the convex portions indicated by the arithmetic mean height (Sa), the degree of sharpness of the tips of the convex portions indicated by the average arithmetic curvature (Spc) of the tips of the convex portions (sharpness of the tips of the convex portions), and the degree of inclination of the uneven structure indicated by the developed area ratio (Sdr) represented by S2 / S1, where S1 is the projected area when the uneven structure is projected onto a flat surface and S2 is the difference between the actual surface area of the uneven structure and the projected area S1. The performance exhibited by specifying the above three surface roughness parameters works together to make the surface of the active energy ray curable resin layer having a fine uneven structure that satisfies these surface parameters suitable for exhibiting both low gloss and antifouling properties, thereby enabling the interior material to achieve both low gloss and antifouling properties.
[0010] In the interior material according to the present invention, It is preferable that the uneven structure further satisfies the surface roughness parameter (4) below. (4) The maximum height (Sz) is 5 to 50 μm.
[0011] According to the interior material of this configuration, the uneven structure further satisfies the surface roughness parameter (4) above, so that the degree of local protrusion (protrusion length) of the protrusions indexed by the maximum height (Sz) becomes suitable for exhibiting both low gloss and antifouling properties. As a result, in addition to the above three surface roughness parameters, the performance exhibited by specifying the maximum height (Sz) works together to make the surface of the active energy ray cured resin layer having the uneven structure more suitable for exhibiting both low gloss and antifouling properties. As a result, the interior material is able to achieve both low gloss and antifouling properties at a high level.
[0012] In the interior material according to the present invention, The active energy ray-curable resin composition preferably contains a polyfunctional urethane acrylate and a polyfunctional acrylate monomer.
[0013] According to the interior material of this configuration, since the active energy ray curable resin composition contains a polyfunctional urethane acrylate and a polyfunctional acrylate monomer, it is possible to obtain a practical interior material that combines the appropriate elasticity derived from the polyfunctional urethane acrylate and the appropriate rigidity derived from the polyfunctional acrylate monomer.
[0014] In the interior material according to the present invention, The ratio (a:b) of the mass (a) of the polyfunctional urethane acrylate to the mass (b) of the polyfunctional acrylate monomer is preferably 10-90:90-10.
[0015] According to the interior material of the present configuration, the ratio (a:b) of the mass (a) of the multifunctional urethane acrylate to the mass (b) of the multifunctional acrylate monomer is 10-90:90-10, so that a better interior material with a good balance between elasticity and rigidity can be obtained.
[0016] The characteristic configuration of the method for producing an interior material according to the present invention for solving the above problems is as follows: The method for producing the interior material, a coating step of coating the active energy ray-curable resin composition on the substrate; a first irradiation step of irradiating the active energy ray-curable resin composition with excimer laser light; a second irradiation step of irradiating ultraviolet rays or electron beams after the first irradiation step; The purpose of this study is to encompass the above.
[0017] According to the manufacturing method for an interior material of this configuration, by including the above-mentioned coating step, the above-mentioned first irradiation step, and the above-mentioned second irradiation step, it is possible to form an active energy ray cured resin layer having a fine uneven structure whose surface roughness parameters satisfy the above-mentioned (1) to (3) on a substrate. As a result, as described above, the performance exhibited by specifying the above-mentioned three surface roughness parameters works together, and the surface of the active energy ray cured resin layer becomes suitable for exhibiting both low gloss and antifouling properties. Therefore, according to the manufacturing method for an interior material, it is possible to manufacture an interior material that achieves both low gloss and antifouling properties. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a cross-sectional view showing a typical laminated structure of an interior material according to one embodiment of the present invention, together with a manufacturing method thereof and an enlarged view of the uneven surface structure. [Diagram 2] FIG. 2 shows an interior material according to Example 1, where FIG. 2(a) is a laser microscope photograph of the surface, and FIG. 2(b) is a three-dimensional image of the area photographed by the laser microscope. [Diagram 3] FIG. 3 shows an interior material according to Example 2, where FIG. 3(a) is a laser microscope photograph of the surface, and FIG. 3(b) is a three-dimensional image of the area photographed with the laser microscope. [Figure 4] FIG. 4 shows an interior material according to Example 3, where FIG. 4(a) is a laser microscope photograph of the surface, and FIG. 4(b) is a three-dimensional image of the area photographed with the laser microscope. [Diagram 5] FIG. 5 shows an interior material according to Comparative Example 1, where FIG. 5(a) is a laser microscope photograph of the surface, and FIG. 5(b) is a three-dimensional image of the area photographed with the laser microscope. [Figure 6] FIG. 6 shows an interior material according to Comparative Example 2, where FIG. 6(a) is a laser microscope photograph of the surface, and FIG. 6(b) is a three-dimensional image of the area photographed with the laser microscope. [Figure 7]FIG. 7 shows an interior material according to Comparative Example 3, where FIG. 7(a) is a laser microscope photograph of the surface, and FIG. 7(b) is a three-dimensional image of the area photographed with the laser microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, an embodiment of the interior material of the present invention will be described with reference to the drawings. In each drawing, the thickness relationship of each layer and the uneven structure are appropriately exaggerated or simplified for ease of explanation, and do not strictly reflect the size relationship (scale) of the thickness of each layer and the uneven structure in an actual interior material.
[0020] In this specification, the "surface" of the active energy ray cured resin layer formed on the substrate refers to the surface opposite to the substrate, i.e., the surface exposed to the outside. In addition, the "active energy ray curable resin (composition)" means an uncured resin or resin composition having the property of being cured by irradiation with active energy rays, and the "active energy ray curable resin" means a resin in a state in which the active energy ray curable resin (composition) is cured by irradiation with active energy rays. The active energy rays used in the embodiment of the present invention are excimer laser light and ultraviolet rays.
[0021] <Overall composition of interior materials> Fig. 1 is a cross-sectional view showing a laminated structure of an interior material 1 according to one embodiment of the present invention, together with a manufacturing method thereof and a concave-convex structure on the surface. The interior material 1 shown in Fig. 1 is an interior material including a base material 2 and an active energy ray cured resin layer 3 made of a cured product of an active energy ray curable resin composition 30 laminated on the base material 2.
[0022] <Base material> The substrate 2 constitutes the main body of the interior material 1, and the active energy ray cured resin layer 3 is laminated on its surface 2a. The material of the substrate 2 is not particularly limited, and examples thereof include resins such as soft polyvinyl chloride and hard polyvinyl chloride, and inorganic materials such as ceramics. The interior material 1 can be used for conventionally known flooring materials, wall materials, and the like. In particular, polyvinyl chloride resin is suitable as a flooring material because of its excellent processability and strength.
[0023] The thickness of the base material 2 is preferably 1 mm or more, and more preferably 5 mm or more. When the thickness of the base material 2 is 1 mm or more, the strength of the interior material 1 is increased. The upper limit of the thickness of the base material 2 is not particularly limited, but can be, for example, 100 mm or less.
[0024] <Active energy ray cured resin layer> As shown in Fig. 1, the active energy ray cured resin layer 3 is made of a cured product of an active energy ray curable resin composition 30 laminated on a substrate 2, and a surface 3a of the active energy ray cured resin layer 3 is configured to have an uneven structure 4. This uneven structure 4 forms wrinkles as shown in Figs. 2 to 4 described later.
[0025] The surface 3a of the active energy ray-cured resin layer 3 has an uneven structure 4 that satisfies the following surface roughness parameters (1) to (3). (1) The arithmetic mean height (Sa) is 0.5 to 6 μm. (2) The average arithmetic curvature (Spc) of the tip of the convex portion 4a is 300 to 1300 μm -1 It is. (3) When the projected area of the uneven structure 4 projected onto a flat surface is S1 and the difference between the actual surface area of the uneven structure 4 and the projected area S1 is S2, the developed area ratio (Sdr) represented by S2 / S1 is 0.05 to 0.2. The present inventors have conducted intensive research into the numerous combinations of various parameters that serve as indicators of the unevenness structure, and have discovered that the performance exhibited by specifying the above surface roughness parameters (1) to (3) works in combination to make the surface of an active energy ray-cured resin layer having a fine unevenness structure that satisfies these surface parameters suitable for exhibiting both low gloss and antifouling properties.
[0026] The arithmetic mean height (Sa) is an index of the overall degree of protrusion (protrusion length) of the convex portions 4a of the concave-convex structure 4. The smaller the arithmetic mean height (Sa), the smaller the overall protrusion length of the convex portions 4a, and accordingly the smaller the overall depth of the concave portions 4b. On the other hand, the larger the arithmetic mean height (Sa), the larger the overall protrusion length of the convex portions 4a, and accordingly the larger the overall depth of the concave portions 4b. When the arithmetic mean height (Sa) is 0.5 to 6 μm, the overall protrusion length of the convex portions 4a becomes suitable for low gloss and antifouling properties. The arithmetic mean height (Sa) is calculated as an average value measured at any ten points on the surface 3a of the active energy ray cured resin layer 3.
[0027] The arithmetic mean height (Sa) is preferably 2 to 5 μm. When the arithmetic mean height (Sa) is 2 to 5 μm, the uneven structure 4 on the surface 3a of the active energy ray cured resin layer 3 has a protrusion degree (protrusion length) of the protrusions 4a indexed by the arithmetic mean height (Sa) that is more suitable for exhibiting both low gloss and antifouling properties. This allows the interior material 1 to achieve both low gloss and antifouling properties at a high level.
[0028] The average arithmetic curvature (Spc) of the tip (apex) of the convex portion 4a is an index of the sharpness of the tip of the convex portion 4a (sharpness of the tip of the convex portion 4a). The average arithmetic curvature (Spc) represents the curvature at the apex when the convex portion 4a is quantified as a quadratic function so as to become a parabola. The smaller the average arithmetic curvature (Spc), the more rounded the tip of the convex portion 4a. On the other hand, the larger the average arithmetic curvature (Spc), the more pointed the tip of the convex portion 4a. When the average arithmetic curvature (Spc) is 300 to 1300 μm -1This makes the convex portions 4a sharper, which is suitable for achieving low gloss and antifouling properties. The average arithmetic curvature (Spc) of the tip of the convex portions 4a is calculated as the average value of measurements taken at any ten points on the surface 3a of the active energy ray-cured resin layer 3.
[0029] The average arithmetic curvature (Spc) is 400 to 1200 μm. -1 It is preferable that the average arithmetic curvature (Spc) is 400 to 1200 μm. -1 As a result, the uneven structure 4 on the surface 3a of the active energy ray cured resin layer 3 has a degree of sharpness of the tips of the protrusions 4a, as indexed by the mean arithmetic curvature (Spc), that is more suitable for exhibiting both low gloss and stain resistance. As a result, the interior material 1 achieves both low gloss and stain resistance at a high level.
[0030] When the projected area of the uneven structure 4 projected onto a flat surface is S1, and the difference between the actual surface area of the uneven structure 4 and the projected area S1 is S2, the developed area ratio (Sdr) represented by S2 / S1 is an index of the degree of inclination of the convex portions 4a and concave portions 4b of the uneven structure 4. The developed area ratio (Sdr) is expressed by the ratio S2 / S1 of the projected area S1 of the uneven structure 4 projected onto a flat surface and the difference (increase) S2 between the actual surface area of the uneven structure 4 and the projected area S1, and is expressed as a numerical value in the range of 0 to 1 (dimensionless). When the developed area ratio (Sdr) is at its smallest (Sdr=0), the difference S2 is 0 and the actual surface area is equal to the projected area S1, so that the uneven structure 4 is not formed on the surface 3a and is not inclined at all. The larger the developed area ratio (Sdr), the larger the difference S2, that is, the actual surface area is larger than the projected area S1, so that the inclination of the convex portion 4a and the concave portion 4b is larger. When the arithmetic mean height (Sa) is the same, the larger the developed area ratio (Sdr), the larger the number of the convex portions 4a and the concave portions 4b, while the smaller the developed area ratio (Sdr), the smaller the number of the convex portions 4a and the concave portions 4b. When the developed area ratio (Sdr) is 0.05 to 0.2, the degree of inclination and the number of the convex portions 4a and the concave portions 4b of the concave-convex structure 4 are suitable for low gloss and antifouling properties. When the projected area of the concave-convex structure 4 projected onto a flat surface is S1, and the difference between the actual surface area of the concave-convex structure 4 and the projected area S1 is S2, the developed area ratio (Sdr) expressed by S2 / S1 is calculated as the average value measured at any ten points on the surface 3a of the active energy ray cured resin layer 3.
[0031] The developed area ratio (Sdr) is preferably 0.06 to 0.17. When the developed area ratio (Sdr) is 0.06 to 0.17, the uneven structure 4 on the surface 3a of the active energy ray cured resin layer 3 has a degree of inclination of the uneven structure 4, which is indexed by the developed area ratio (Sdr), that is more suitable for exhibiting both low gloss and antifouling properties. As a result, the interior material 1 achieves both low gloss and antifouling properties at a high level.
[0032] By having the uneven structure 4 satisfying the surface roughness parameters (1) to (3) above, the uneven structure 4 on the surface 3a of the active energy ray curable resin layer 3 becomes suitable for exhibiting both low gloss and anti-fouling properties in terms of the degree of protrusion (protrusion length) of the convex portions 4a indexed by the arithmetic mean height (Sa), the degree of sharpness (sharpness of the tips of the convex portions 4a) of the tips of the convex portions 4a indexed by the average arithmetic curvature (Spc) of the tips of the convex portions 4a, and the degree of inclination of the uneven structure 4 indexed by the developed area ratio (Sdr) expressed as S2 / S1, where S1 is the projected area when the uneven structure 4 is projected onto a flat surface and S2 is the difference between the actual surface area of the uneven structure 4 and the projected area S1. That is, the performance exhibited by specifying the above three surface roughness parameters works together, and the surface 3a of the active energy ray cured resin layer 3 having the fine uneven structure 4 that satisfies these surface roughness parameters becomes suitable for exhibiting both low gloss and antifouling properties. As a result, the interior material 1 achieves both low gloss and antifouling properties.
[0033] Furthermore, by having the uneven surface structure 4 that satisfies the surface roughness parameters (1) to (3) above, chemical resistance is also achieved. This is believed to be because the uneven surface structure 4 provides a water repellent effect due to the lotus effect, making it possible to reduce the amount of chemicals that come into contact with the surface 3a of the active energy ray cured resin layer 3. In addition, the increased density of the surface 3a of the active energy ray cured resin layer 3 is also believed to contribute to the improvement of chemical resistance.
[0034] It is preferable that the uneven structure 4 further satisfies the surface roughness parameter (4) below. (4) The maximum height (Sz) is 5 to 50 μm.
[0035] The maximum height (Sz) is an index of the degree of local protrusion (protrusion length) of the convex portion 4a of the concave-convex structure 4. When the arithmetic mean height (Sa) is the same, the smaller the maximum height (Sz), the smaller the overall protrusion length of the convex portion 4a, and accordingly the overall depth of the concave portion 4b also becomes smaller. On the other hand, when the arithmetic mean height (Sa) is the same, the larger the maximum height (Sz), the larger the protrusion length of the convex portion 4a becomes locally, and accordingly the depth of the concave portion 4b becomes locally larger. In other words, even if the arithmetic mean height (Sa) is the same, the smaller the maximum height (Sz), the more homogenized the degree of protrusion of the concave-convex structure 4 is. When the maximum height (Sz) is 5 to 50 μm, the degree of local protrusion (protrusion length) of the convex portion 4a indexed by the maximum height (Sz) becomes suitable for exhibiting both low gloss and antifouling properties. As a result, in addition to the above three surface roughness parameters, the performance exhibited by specifying the maximum height (Sz) works in combination to make the surface 3a of the active energy ray cured resin layer 3 having the concave-convex structure 4 more suitable for exhibiting both low gloss and antifouling properties. As a result, the interior material 1 achieves both low gloss and antifouling properties at a high level. In addition, since the degree of protrusion of the concave-convex structure 4 is made uniform, chemical resistance is improved. The maximum height (Sz) is calculated as an average value measured at any ten points on the surface 3a of the active energy ray cured resin layer 3.
[0036] The maximum height (Sz) is preferably 15 to 45 μm. By setting the maximum height (Sz) to 15 to 45 μm, the uneven structure 4 on the surface 3a of the active energy ray cured resin layer 3 has a reduced degree of local protrusion (protrusion length) of the protrusions 4a, which is indicated by the maximum height (Sz), and the uneven structure 4 is homogenized overall, which is more suitable for achieving both low gloss and antifouling properties. As a result, the interior material 1 achieves both low gloss and antifouling properties at a higher level.
[0037] As described above, the surface 3a of the active energy ray cured resin layer 3 has the uneven structure 4 that satisfies the above surface roughness parameters, so that the layer 3a can exhibit low gloss and antifouling properties even without containing powder such as silica. However, the active energy ray cured resin layer 3 may contain powder such as silica as long as it does not interfere with the low gloss and antifouling properties provided by the uneven structure 4.
[0038] Examples of the active energy rays used in the present invention include light rays such as far ultraviolet rays, ultraviolet rays, near ultraviolet rays, infrared rays, excimer laser light, electromagnetic waves such as X-rays and gamma rays, as well as electron beams, proton beams, and neutron beams. The active energy ray curable resin used in the present invention refers to a resin crosslinked and cured by irradiation with active energy rays, and can be obtained by irradiating an active energy ray curable resin composition with active energy rays by a known method. Among active energy ray curable resins, ultraviolet ray curable resins or electron beam curable resins are preferably used, and ultraviolet ray curable resins are more preferably used because they are excellent in processability and easy to handle.
[0039] The active energy ray curable resin contained in the active energy ray curable resin composition 30 is not particularly limited and can be appropriately set. For example, the active energy ray curable resin composition 30 preferably contains a polyfunctional urethane acrylate and a polyfunctional acrylate monomer. By containing the active energy ray curable resin composition 30 with the polyfunctional urethane acrylate and the polyfunctional acrylate monomer, it is possible to obtain a practical interior material 1 having both the appropriate elasticity derived from the polyfunctional urethane acrylate and the appropriate rigidity derived from the polyfunctional acrylate monomer.
[0040] Examples of the polyfunctional urethane acrylate include bifunctional urethane acrylate, trifunctional urethane acrylate, tetrafunctional urethane acrylate, pentafunctional urethane acrylate, and hexafunctional urethane acrylate, and bifunctional urethane acrylate is preferred. By using a bifunctional urethane acrylate as the polyfunctional urethane acrylate, a practical interior material 1 having a high level of appropriate elasticity derived from the polyfunctional urethane acrylate can be obtained. Specific examples of polyfunctional urethane acrylates include, for example, phenyl glycidyl ether (meth)acrylate hexamethylene diisocyanate urethane prepolymer, phenyl glycidyl ether (meth)acrylate isophorone diisocyanate urethane prepolymer, phenyl glycidyl ether (meth)acrylate tolylene diisocyanate urethane prepolymer, glycerin di(meth)acrylate tolylene diisocyanate urethane oligomer, pentaerythritol tri(meth)acrylate hexamethylene diisocyanate urethane oligomer, glycerin di(meth)acrylate isophorone diisocyanate urethane oligomer, pentaerythritol tri(meth)acrylate tolylene diisocyanate urethane oligomer, pentaerythritol tri(meth)acrylate isophorone diisocyanate urethane preoligomer, etc. These may be used alone or in combination of two or more.
[0041] Examples of the polyfunctional acrylate monomer include a bifunctional acrylate monomer, a trifunctional acrylate monomer, a tetrafunctional acrylate monomer, a pentafunctional acrylate monomer, and a hexafunctional acrylate monomer, and a trifunctional acrylate monomer is preferable. By using a trifunctional acrylate monomer as the polyfunctional acrylate monomer, a practical interior material 1 having a high level of appropriate rigidity derived from the trifunctional acrylate monomer can be obtained. In addition, the concave-convex structure 4 that satisfies the above surface roughness parameters (1) to (3), and further (4), can be obtained more reliably. Examples of polyfunctional acrylate monomers include ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, propylene glycol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, 1,3-propanediol diacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, glycerol triacrylate, trimethylolethane triacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, dipentaerythritol triacrylate, etc. These may be used alone or in combination of two or more.
[0042] The ratio (a:b) of the mass (a) of the polyfunctional urethane acrylate to the mass (b) of the polyfunctional acrylate monomer is, for example, 10 to 90:90 to 10, preferably 20 to 80:80 to 20, and more preferably 30 to 70:70 to 30. When the ratio (a:b) of the mass (a) of the polyfunctional urethane acrylate to the mass (b) of the polyfunctional acrylate monomer is within the above range, a more excellent interior material 1 can be obtained that has an appropriate viscosity, excellent application ability, and a good balance between elasticity and rigidity.
[0043] The total content of the polyfunctional urethane acrylate and the polyfunctional acrylate monomer in the active energy ray curable resin composition 30 is preferably 90% by mass or more, and more preferably 93% by mass or more. By having the total content of the polyfunctional urethane acrylate and the polyfunctional acrylate monomer in the active energy ray curable resin composition 30 be 90% by mass or more, the above-mentioned elasticity and rigidity due to the polyfunctional urethane acrylate and the polyfunctional acrylate monomer can be more effectively exhibited.
[0044] The active energy ray curable resin composition 30 preferably contains a polymerization initiator. By containing the active energy ray curable resin composition 30, after forming the uneven structure 4 on the surface 3a of the interior material 1, the active energy ray curable resin composition 30 can be reliably cured up to a deep part where the active energy ray is difficult to reach. As a result, the strength of the interior material 1 is improved, and the practicality can be improved. As the polymerization initiator, a polymerization initiator capable of polymerization without light irradiation can be used. As such a polymerization initiator, for example, radical polymerization initiators such as benzoyl peroxide and azobisisobutyronitrile, in which polymerization is initiated by radicals generated by heating, can be mentioned. In a shallow part where the active energy ray reaches, it is of course possible to use a photopolymerization initiator such as benzophenone, commercially available products Omnirad 754, Omnirad 184, and Omnirad 127 (manufactured by IGM Resins BV). The content of the polymerization initiator in the active energy ray curable resin composition 30 is preferably 1 to 10 mass%, more preferably 1 to 7 mass%.
[0045] The active energy ray curable resin composition 30 may contain any additive as long as it does not impair the low gloss and antifouling properties provided by the above-mentioned unevenness structure 4. For example, the active energy ray curable resin composition 30 may contain a conventionally known organic solvent or the like for adjusting the viscosity by dilution or the like.
[0046] The thickness of the active energy ray cured resin layer 3 is preferably 5 to 50 μm, and more preferably 10 to 25 μm. When the thickness of the active energy ray cured resin layer 3 is equal to or greater than the above lower limit, the active energy ray cured resin layer 3 can have a uniform thickness. When the thickness of the active energy ray cured resin layer 3 is equal to or less than the above upper limit, it becomes easy to form an uneven structure 4 that can exhibit low gloss and antifouling properties.
[0047] The glossiness (60°) of the surface 3a of the active energy ray cured resin layer 3 is preferably 5% or less. When the glossiness of the surface 3a of the active energy ray cured resin layer 3 is 5% or less, the interior material 1 has excellent low gloss properties, and dirt and scratches are less noticeable. The glossiness (60°) is measured by the measurement method described below.
[0048] <Characteristics of interior materials> The surface roughness parameters (Sa), (Spc), (Sdr), and (Sz) of the surface 3a of the active energy ray-cured resin layer 3 in the interior material 1, as well as the gloss (60°), are as described above.
[0049] <Manufacturing methods for interior materials> The manufacturing method of the interior material 1 includes a manufacturing method including a coating step of coating the active energy ray curable resin composition 30 on the substrate 2, a first irradiation step of irradiating the active energy ray curable resin composition 30 with excimer laser light, and a second irradiation step of irradiating ultraviolet light or electron beams after the first irradiation step. Such a manufacturing method of the interior material 1 will be described with reference to Figs. 1(a) to (c).
[0050] First, as shown in Fig. 1(a), an uncured active energy ray curable resin composition 30 is applied as a coating liquid to the surface 2a of the substrate 2 (coating step). The coating thickness of the active energy ray curable resin composition 30 on the substrate 2 may be appropriately set so that the thickness of the active energy ray cured resin layer 3 as a cured body has a desired value, and can be, for example, 10 to 50 µm, preferably 15 to 25 µm, in accordance with the above-mentioned thickness of the active energy ray cured resin layer 3. The coating method is not particularly limited, and various coater methods such as a roll coater, a blade coater, and a curtain coater are suitably used.
[0051] Next, as shown in FIG. 1(b), the surface 30a of the applied active energy ray curable resin composition 30 is irradiated with excimer laser light (shown as "EL" in FIG. 1(b)) from an excimer laser light irradiation device 51 (first irradiation step). Excimer laser light is light with a single wavelength peak that is emitted when an excited state molecule (excimer) composed of an excited state atom and a ground state atom dissociates into two atoms. Examples of excimer laser light include excimer laser light with a wavelength of 126 nm emitted from an Ar2 excimer, excimer laser light with a wavelength of 146 nm emitted from a Kr2 excimer, excimer laser light with a wavelength of 157 nm emitted from an F2 excimer, excimer laser light with a wavelength of 172 nm emitted from an Xe2 excimer, and excimer laser light with a wavelength of 193 nm emitted from an ArF excimer. By using such an excimer laser light, only the surface 30a of the active energy ray curable resin composition 30 can be partially cured. In this embodiment, an excimer laser light with a wavelength of 172 nm can be used. Due to its short wavelength, the excimer laser light cannot reach the inside of the active energy ray curable resin composition 30. Therefore, the surface 30a of the active energy ray curable resin composition 30 is selectively cured by irradiation with the excimer laser light. While the surface 30a of the active energy ray curable resin composition 30 shrinks as it is cured, the inside does not harden and does not shrink, so this difference in contraction force is alleviated by the formation of local protuberances, i.e., unevenness, on the surface 30a. The unevenness that occurs with the relaxation of the contraction force can be regarded as wrinkles. In other words, the uneven structure can also be said to be wrinkles. In this way, a surface-cured body (active energy ray curable resin composition with a cured surface) 31 is formed as an intermediate body in which the surface is cured to have an uneven structure 41 while the inside is uncured. The irradiation conditions of the excimer laser light are not particularly limited, but for example, the peak irradiance is 70 to 100 mW / cm 2 , cumulative light amount is 50~200mJ / cm 2 can be set to.
[0052] Next, as shown in FIG. 1(c), the surface 31a of the surface-cured body 31 is irradiated with ultraviolet light (shown as "UV" in FIG. 1(c)) from an ultraviolet light irradiation device 52 (second irradiation step). The ultraviolet light has a wavelength longer than that of the excimer laser light. Examples of such ultraviolet light include ultraviolet light with a wavelength of 300 to 400 nm. The ultraviolet light can reach the inside of the surface-cured body 31, so that the entire body is cured (i.e., completely cured), and an active energy ray-cured resin layer 3 is obtained as a completely cured body having an uneven structure 4 on its surface. The uneven structure 41 on the surface 31a of the surface-cured body 31 becomes the uneven structure 4 on the surface 3a of the active energy ray-cured resin layer 3 in a substantially unchanged state. The uneven structure 4 has a plurality of convex portions 4a and a plurality of concave portions 4b. As for the irradiation conditions of the ultraviolet light, it is preferable that both the peak irradiance and the integrated light amount are greater than the peak irradiance and the integrated light amount of the excimer laser light, respectively. In this case, for example, the peak irradiance of the ultraviolet light is set to 90 to 130 mW / cm 2 , cumulative light amount is 400~800mJ / cm 2 Curing with ultraviolet light is preferable from the viewpoint of improving production efficiency because it provides excellent processability during production.
[0053] In this manner, the uncured active energy ray curable resin composition 30 is applied as a coating liquid onto the substrate 2, the surface 30a of the applied active energy ray curable resin composition 30 is irradiated with excimer laser light, and then ultraviolet light is irradiated, thereby obtaining an interior material 1 in which an active energy ray curable resin layer 3 is formed on the substrate 2.
[0054] According to the manufacturing method of the interior material 1, by including the above-mentioned application step, the above-mentioned first irradiation step, and the above-mentioned second irradiation step, it is possible to form an active energy ray cured resin layer 3 having a fine uneven structure 4 whose surface roughness parameters satisfy the above-mentioned (1) to (3) on a substrate 2. As a result, the performance exhibited by specifying the above-mentioned three surface roughness parameters works together, and the surface 3a of the active energy ray cured resin layer 3 becomes suitable for exhibiting both low gloss and antifouling properties. Therefore, according to the manufacturing method of the interior material 1, it is possible to manufacture an interior material 1 that achieves both low gloss and antifouling properties.
[0055] The surface roughness parameters in the uneven structure 4 of the surface 3a of the active energy ray curable resin layer 3 are set so as to satisfy the above (1) to (3), and preferably so as to satisfy the above (4), by appropriately setting the above-mentioned type of active energy ray curable resin, the irradiation conditions of the excimer laser light, the irradiation conditions of the ultraviolet light, etc. Also, the excimer laser light and the ultraviolet light may be irradiated while moving the laminate of the substrate 2 and the active energy ray curable resin composition 30 applied on the substrate 2, and in this case, the accumulated light amount of each can be adjusted by appropriately setting the line speed.
[0056] 1(c) shows an example of irradiating with ultraviolet rays, but is not limited thereto, and may be irradiated with an electron beam (EB) instead of ultraviolet rays. In this case, the active energy ray curable resin composition 30 does not require the addition of a photopolymerization initiator. EXAMPLES
[0057] Interior materials having the characteristic features of the present invention (Examples 1 to 3) were produced and various measurements and evaluations were carried out. For comparison, interior materials not having the characteristic features of the present invention (Comparative Examples 1 to 3) were produced and similar measurements and evaluations were carried out.
[0058] [Examples 1 to 3] As the ultraviolet-curable resin as the active energy ray-curable resin (hereinafter, the same applies in the Examples and Comparative Examples), a bifunctional urethane acrylate and a trifunctional acrylate monomer were used. These bifunctional urethane acrylate and trifunctional acrylate monomer were mixed with a polymerization initiator in the amounts shown in Table 1 to obtain an active energy ray-curable resin composition. The obtained active energy ray-curable resin composition was applied to a hard polyvinyl chloride tile as a substrate to a thickness of 25 μm, and irradiated with an excimer laser beam and then with ultraviolet light under the irradiation conditions shown in Table 1 to obtain interior materials of Examples 1 to 3 in which an active energy ray-curable resin layer was laminated on the substrate.
[0059] [Comparative Example 1] An interior material of Comparative Example 1 was obtained in the same manner as in Example 1, except that the irradiation conditions for the excimer laser light were set to those shown in Table 1.
[0060] [Comparative Example 2] An active energy ray-curable resin composition was obtained in the same manner as in Example 1, except that a monofunctional acrylate monomer was used instead of the trifunctional acrylate monomer in the blending amount shown in Table 1. The obtained active energy ray-curable resin composition was applied to a hard polyvinyl chloride tile as a substrate to a thickness of 25 μm, and irradiated with excimer laser light and then ultraviolet light under the irradiation conditions shown in Table 1, thereby obtaining an interior material of Comparative Example 2 in which an active energy ray-curable resin layer was laminated on the substrate.
[0061] [Comparative Example 3] An active energy ray-curable resin composition was obtained in the same manner as in Example 1, except that in addition to the active energy ray-curable resin and the polymerization initiator, matte silica was further used as powder and mixed in the amounts shown in Table 1. The obtained active energy ray-curable resin composition was applied to a hard polyvinyl chloride tile as a substrate to a thickness of 25 μm, and irradiated with ultraviolet rays under the irradiation conditions shown in Table 1 without irradiating with excimer laser light, thereby obtaining an interior material of Comparative Example 3 in which an active energy ray-curable resin layer having matte silica (powder) was laminated on the substrate.
[0062] Photographs and three-dimensional images of the interior materials of Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Figs. 2 to 7. Fig. 2(a) is a laser microscope photograph of the surface of the active energy ray cured resin layer, and Fig. 2(b) is a three-dimensional image of the area photographed by the laser microscope, and both show the same range on the surface. That is, Fig. 2 shows a rectangular surface, but Fig. 2(b) shows that the long side is 277.243 μm and the short side is 207.32 μm, and these dimensions correspond to the long side and short side dimensions of the rectangle in Fig. 2(a). Fig. 2(b) also shows that the dimensions from the reference plane are 17.66 μm and -25.398 μm, but the sum of the absolute values of both shows the dimension from the peak of the mountain to the bottom of the valley in the uneven structure. The numerical values shown in Figs. 3 to 7 are also the same as those in Fig. 2. Figs. 2 to 7 are photographs and three-dimensional images at one point out of ten points in each of Examples 1 to 3 and Comparative Examples 1 to 3.
[0063] The measurement and evaluation items in Examples 1 to 3 and Comparative Examples 1 to 3 are the arithmetic mean height (Sa), maximum height (Sz), and average arithmetic curvature (Spc) of the tips of the convex portions as surface roughness parameters on the surface of the active energy ray cured resin layer, and the developed area ratio (Sdr) expressed as S2 / S1, where S1 is the projected area when the concave-convex structure is projected onto a flat surface and S2 is the difference between the actual surface area of the concave-convex structure and the projected area S1, as well as glossiness, antifouling property, and chemical resistance. Each item will be explained below.
[0064] [Surface roughness parameters] Using a laser microscope equipped with a white light interferometer VK-X3000 (manufactured by Keyence Corporation), the surface of the active energy ray cured resin layer in the obtained interior material was photographed at a magnification of 50 times, and analyzed using the attached analysis tool. As a result, a photograph of the surface of the active energy ray cured resin layer and a 3D image of the photographed area were obtained, and the arithmetic mean height (Sa), maximum height (Sz), average arithmetic curvature of the tip of the convex part (Spc), and the developed area ratio (Sdr), expressed as S2 / S1, were obtained as surface roughness parameters, where S1 is the projected area when the uneven structure is projected onto a flat surface, and S2 is the difference between the actual surface area of the uneven structure and the projected area S1.
[0065] [Glossiness] The obtained interior material was cut into a square shape of 300 mm length × 300 mm width to obtain a test piece. The test piece was aged for 24 hours under conditions of a temperature of 23°C ± 2°C and a humidity of 70% ± 15%, and then the gloss (60°) of five arbitrary points on the surface of the active energy ray cured resin layer of the test piece was measured using a gloss meter (model: IG-320, manufactured by Horiba, Ltd.), and the average value was calculated.
[0066] [Anti-stain properties (heel mark test)] The obtained interior material was cut into a square shape of 22 cm long x 22 cm wide to obtain a test piece. The surface of the substrate of the three test pieces (the surface opposite to the active energy ray cured resin layer) was attached to the inner wall of a hollow container in the shape of a regular hexagonal prism. Six cubic rubber pieces of 5 cm long x 5 cm wide x 5 cm high were placed in the hollow container, and the hollow container was rotated clockwise for 15 minutes (rotation speed: 63 rpm), and then rotated counterclockwise for 15 minutes (rotation speed: 63 rpm) to perform a heel mark test. After the rotation was stopped, the test piece was taken out and visually observed under the following three conditions, and evaluated according to the following criteria. <Condition> Condition 1: Immediately after heel mark test (no wiping, immediately after test) Condition 2: After wiping with a dry cloth (after dry wiping) Condition 3: After wiping with a cloth dampened with water (after wiping with water) <Judgment criteria> A: No heel marks at all (good) B: There are a few heel marks (slightly bad) C: Many heel marks are attached (bad)
[0067] [Chemical resistance] The obtained interior material was cut into a square shape of 10 cm long x 10 cm wide to obtain a test piece. A square piece of absorbent cotton of 1.5 cm x 1.5 cm with a thickness of about 5 mm was placed in the center of each test piece, and 1.0 mL of povidone-iodine (trade name: Isodine (registered trademark)) was soaked into the entire absorbent cotton. After the test piece and the absorbent cotton were sufficiently attached to each other, a watch glass with a diameter of 9.0 cm was placed on the test piece so as to cover the absorbent cotton, and the test piece was left to stand for 24 hours, after which the absorbent cotton was removed and the surface of the test piece was washed with distilled water. After this treatment, the test piece was visually observed and evaluated according to the following criteria. <Judgment criteria> A: Not colored (good) B: Slightly discolored (slightly poor) C: Highly colored (bad)
[0068] The configurations of the interior materials of Examples 1 to 3 and Comparative Examples 1 to 3, as well as the measurement results and evaluation results, are shown in Table 1. In Table 1, the unit of integrated light quantity is "mJ / cm 2 " and the unit of peak illuminance is "mW / cm 2 "
[0069] [Table 1]
[0070] The interior materials of Examples 1 to 3 have surface roughness parameters of the surface of the active energy ray curable resin layer, with an arithmetic mean height (Sa) of 0.5 to 6 μm and a mean arithmetic curvature (Spc) of 300 to 1300 μm. -1and the developed area ratio (Sdr) was 0.05 to 0.2. The maximum height (Sz) was 5 to 50 μm. The interior materials of Examples 1 to 3 had a gloss (60°) of 5% or less, which means they had excellent low gloss properties, and the stain resistance was evaluated as A under all three conditions, immediately after the test, after dry wiping, and after wiping with water, which showed that they also had excellent stain resistance. The interior materials of Examples 1 to 3 also had a chemical resistance evaluation of A, which showed that they also had excellent chemical resistance.
[0071] In contrast, the interior material of Comparative Example 1 exceeded the above-mentioned numerical ranges for the average arithmetic curvature (Spc) and the developed area ratio (Sdr) among the above-mentioned surface roughness parameters. FIG. 5 shows that, although relatively neat wrinkles are formed on the surface of the active energy ray cured resin layer, the wrinkles are dense and have large height differences. The interior material of Comparative Example 1 has a gloss level of 5% or less, which means that it has excellent low gloss properties, but its stain resistance was evaluated as C immediately after the test, which shows that it has poor stain resistance. Furthermore, the interior material of Comparative Example 1 was evaluated as B in chemical resistance, which shows that it has poor chemical resistance.
[0072] The interior material of Comparative Example 2 had the arithmetic mean height (Sa), mean arithmetic curvature (Spc), and developed area ratio (Sdr) of the above surface roughness parameters that exceeded the above numerical ranges. FIG. 6 shows that wrinkles were not formed uniformly on the surface of the active energy ray cured resin layer, but were formed locally. The interior material of Comparative Example 2 had a gloss level of more than 5%, which was poor in low gloss, and was rated C immediately after the test and B after dry wiping, which indicated that the interior material had poor stain resistance. The interior material of Comparative Example 2 also had a B rating for chemical resistance, which indicated that the interior material had poor chemical resistance.
[0073] The interior material of Comparative Example 3 had all of the above surface roughness parameters that did not meet the above numerical ranges. Specifically, the arithmetic mean height (Sa) and maximum height (Sz) were small, so the protruding length of the convex parts was small, the average arithmetic curvature (Spc) was small, so the sharpness of the convex parts was small, and the developed area ratio (Sdr) was close to 0, so the surface was close to a flat surface. FIG. 7 shows that although very fine convex parts derived from matte silica were formed on the surface of the active energy ray cured resin layer, the surface was substantially flat. The interior material of Comparative Example 3 had a glossiness of more than 5%, which was poor in low glossiness, and the evaluation of the antifouling property was C immediately after the test, which indicated that the antifouling property was poor. In addition, the interior material of Comparative Example 3 was evaluated as C in chemical resistance, which indicated that the chemical resistance was poor. [Industrial Applicability]
[0074] The present invention is a technology that can be widely used as an interior material in the construction industry, remodeling industry, and the like, and is particularly useful in installing interior materials, particularly floor materials, in various structures such as ordinary houses, apartment buildings, condominiums, commercial malls, office buildings, factories, stores, stations, schools, hospitals, and public facilities. [Explanation of symbols]
[0075] 1 Interior materials 2 Base material 3. Active energy ray curing resin layer 3a surface 30. Active energy ray-curable resin composition 4 Uneven structure
Claims
1. An interior material comprising a substrate and an active energy ray-cured resin layer laminated on the substrate, the active energy ray-curable resin layer being made of a cured product of an active energy ray-curable resin composition, The active energy ray-curable resin composition contains a polyfunctional urethane acrylate and a polyfunctional acrylate monomer, The surface of the active energy ray curable resin layer has an uneven structure in the form of wrinkles that satisfies the surface roughness parameter (3) below. (3) When the projected area of the uneven structure projected onto a flat surface is S1 and the difference between the actual surface area of the uneven structure and the projected area S1 is S2, the developed area ratio (Sdr) represented by S2 / S1 is 0.05 to 0.
2.
2. The interior material according to claim 1 , wherein the uneven structure further satisfies the following surface roughness parameter (4): (4) The maximum height (Sz) is 5 to 50 μm.
3. The interior material according to claim 1 or 2, wherein the uneven structure further satisfies the following surface roughness parameter (2): (2) The average arithmetic curvature (Spc) of the tip of the convex portion is 300 to 1300 μm -1 It is.
4. The interior material according to claim 1 or 2, wherein the uneven structure further satisfies the following surface roughness parameter (1): (1) The arithmetic mean height (Sa) is 0.5 to 6 μm.
5. 5. The interior material according to claim 1, wherein the surface of the active energy ray-cured resin layer has a glossiness (60°) of 5% or less.
6. A method for producing an interior material according to any one of claims 1 to 5, a coating step of coating the active energy ray-curable resin composition on the substrate; a first irradiation step of irradiating the active energy ray-curable resin composition with excimer laser light; a second irradiation step of irradiating ultraviolet rays or electron beams after the first irradiation step; A method for manufacturing an interior material comprising the steps of:
Citation Information
Patent Citations
Decorative sheet and method for producing the same
JP2021024102A
Matte article and method for manufacturing same
JP2022008024A
Matte article
JP2022048109A
Decorative sheet and decorative material
JP2023049868A
Decorative sheet
JP2023051146A